2021
DOI: 10.1055/a-1295-0752
|View full text |Cite
|
Sign up to set email alerts
|

17-Hydroxyprogesterone Caproate for the Prevention of Recurrent Preterm Birth – A Systematic Review and Meta-analysis Taking into Account the PROLONG Trial

Abstract: Background Prior spontaneous preterm birth is a strong risk factor for the recurrence of spontaneous preterm birth in a subsequent pregnancy and has been evaluated in prevention studies using progesterone (natural progesterone administered orally or vaginally, and 17-hydroxyprogesterone caproate [17-OHPC]) as a selection criterion. Based on the findings of a randomized, placebo-controlled study, 17-OHPC was approved for use in 2011 by the Food and Drug Administration in the USA for the prevention of recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…There have been 2 recent studies on the use of 17-hydroxyprogesterone caproate (17-OHPC) by injection for women with recurrent pregnancy loss [ 21 , 42 ]. In 2021, a meta-analysis that included these 2 studies showed that 17-OHPC injection was not recommended to prevent pregnancy loss or recurrent miscarriage [ 43 ]. A 2016 study enrolled pregnant women at risk of premature birth and randomized them to receive intramuscular 17-OHPC or vaginal micronized progesterone [ 44 ], showing no significant difference between intramuscular 17-OHPC or vaginal micronized progesterone (RR=1.31; 95% CI 0.47–3.66; P =0.59) [ 44 ].…”
Section: Progesterone and Prevention Of Recurrent Miscarriagementioning
confidence: 99%
“…There have been 2 recent studies on the use of 17-hydroxyprogesterone caproate (17-OHPC) by injection for women with recurrent pregnancy loss [ 21 , 42 ]. In 2021, a meta-analysis that included these 2 studies showed that 17-OHPC injection was not recommended to prevent pregnancy loss or recurrent miscarriage [ 43 ]. A 2016 study enrolled pregnant women at risk of premature birth and randomized them to receive intramuscular 17-OHPC or vaginal micronized progesterone [ 44 ], showing no significant difference between intramuscular 17-OHPC or vaginal micronized progesterone (RR=1.31; 95% CI 0.47–3.66; P =0.59) [ 44 ].…”
Section: Progesterone and Prevention Of Recurrent Miscarriagementioning
confidence: 99%
“…Existem poucos estudos que avaliam alternativas à via vaginal para administração da progesterona 1 . Kuon et al 57 realizaram revisão sistemática e metanálise que incluiu o PROLONG Study (Estudo duplo cego, placebo controlado e randomizado, multicêntrico, que avaliou o efeito do 17-OHPC na redução do parto pré-termo recorrente e da morbidade neonatal em gestação única com parto pré-termo prévio), concluindo que o 17-OHPC não pode ser recomendado para a prevenção de partos pré-termos recorrentes, sendo necessários mais estudos randomizados, controlados por placebo, com fatores de risco claramente definidos e comparáveis, para identificar o grupo de mulheres grávidas que poderia se beneficiar do uso de 17-OHPC 57 .…”
Section: Progesteronaunclassified
“…Initial reports and experience with progesterone or 17-alpha hydroxyprogesterone caproate supplementation for women with a high risk of preterm birth (previous preterm birth or short cervix) suggested potential therapeutic benefit (for example, (Epppic Group, 2021;Meis et al, 2003). Other evidence, though, has called these earlier findings into question and has also revealed potential adverse consequences of progesterone treatment such as the risk for cancer in the offspring of treated pregnancies (Kuon, Berger, & Rath, 2021;Murphy, Cirillo, Krigbaum, & Cohn, 2022;Norman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%